Swirling Flows and Flames - Boushaki, Toufik (IntechOpen, 2019)
Swirl flows are used in a wide range of industrial applications. In non-reacting cases, examples of applications include vortex amplifiers and reactors, heat exchangers, jet pumps, and cyclone separators. In reacting cases, swirlers are widely used in combustion systems, such as gas turbines, industrial furnaces, boilers, gasoline and diesel engines, and many other practical heating devices. Effects of using swirl on flow and combustion are significant and varied, and concern, for example, aerodynamics, mixing, flame stability, intensity of combustion, and pollutant emissions. The purpose of this book is to present recent research efforts to understand and characterize swirling flows of different types and in different applications. These include gaseous, liquid, and solid fuels in order to enhance combustion systems and their energy efficiency. Swirl flows are very complex and the studies proposed in this project are based on different means, including theoretical calculations, numerical modeling, and experimental measurements.